2019
DOI: 10.1159/000502767
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Diphenhydramine against Traumatic Brain Injury in Rats via Modulation of Oxidative Stress and Inflammation

Abstract: Background: Traumatic brain injury (TBI) is considered a major burden across the globe affecting both individuals and their families. Therefore, the present study was conducted to determine the protective effect of diphenhydramine (DPM) against TBI in experimental rats. Methods: The effect of DPM was evaluated on the cerebral edema (CE) and neuronal degeneration after the induction of experimental brain injury in rats. The effect of DPM was also investigated on the inflammatory cytokines, for example, tumor ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In contrast, the time of secondary injury is relatively long, providing a treatment window. In the course of pathology, oxidative stress is considered as the core link of secondary injury [ 4 ]. Reactive oxygen species (ROS) are important substances involved in oxidative stress [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the time of secondary injury is relatively long, providing a treatment window. In the course of pathology, oxidative stress is considered as the core link of secondary injury [ 4 ]. Reactive oxygen species (ROS) are important substances involved in oxidative stress [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is involved in the pathogenic processes of numerous central nervous system disorders, including cerebral ischemia, Parkinson's disease, and TBI. A study on TBI induced using a weight-drop model found that acute inhibition of post-traumatic TNF-α production or administration of TNF-binding protein decreased edema, cortical tissue damage, and hippocampal neurodegeneration during the acute post-traumatic period [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This drug also exhibits other pharmacological abilities, including sedative, anticancer, antiemetic, local anesthetic, and anticholinergic activities. DPM is also known to have significant antioxidant activity [ 4 , 5 ]. The purpose of this study was to investigate the role of DPM in inhibiting the post-TBI inflammatory reaction by assessing TNF-α levels as one of the important parameters involved in the inflammatory process.…”
Section: Introductionmentioning
confidence: 99%